Analysis of partner turnover rate and the lifetime number of sexual partners in Cape Town using generalized linear models - Olojede, Christianah Oyindamola (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017